When good jobs go bad : globalization, de-unionization, and declining job quality in the North American auto industry - Rothstein, Jeffrey S. (Rutgers University Press, 2016)
In When Good Jobs Go Bad, Jeffrey Rothstein looks at the impact of globalization on workers in the North American auto industry, revealing that globalization has had a deleterious effect on even the most valued of blue-collar jobs. Rothstein shows how the consolidation of the Mexican and U.S.-Canadian auto industries, the expanding number of foreign automakers in North America, and the spread of lean production have all undermined organized labor and harmed workers.